(untitled) (Ustozlar uchun, 2026)
This article explores effective teaching methods in higher education, highlighting key requirements and barriers. The study examines pedagogical strategies that enhance student engagement and learning outcomes. Additionally, it discusses challenges faced by educators, including technological constraints, student diversity, and institutional limitations. The findings provide practical insights for improving teaching effectiveness in higher education institutions.